Decentralization By Local Governments In The Face Of The Covid-19 Pandemic - aschari cahyaditama (JURNAL TERAPAN PEMERINTAHAN MINANGKABAU, 2022)
Decentralization that has been running for almost 20 years is now being tested with the presence of the Covid-19 pandemic. The implementation of decentralization has encountered various obstacles, especially in handling Covid-19, starting from the relationship between local authorities and central government, the limited resources of each region, the distribution distances in handling COVID-19 needs, and also the varied responses and understanding of the people of each region towards Covid-19. Therefore, extra efforts are needed from the central government and local governments in making regulations that encourage dialogue and negotiations between the government and regions to handle the pandemic situation more effectively. Necessary consideration that different region has particular requirements that the central authority’s policy sometimes failed to meet. Furthermore, government policies should be able to bring out more innovations in handling Covid-19 in each region. This innovation is useful in dealing with the limitations and different contexts of each region in dealing with Covid-19.